Dynamics Of Sustainable Islamic Finance Development: A Bibliometric Analysis And Systematic Literature Review - Citra Etika (Journal of Accounting Inaba, 2026)
This study aims to analyze the dynamics and direction of development in Sustainable Islamic Finance through a combined approach of bibliometric analysis and a systematic literature review of 53 international scientific publications (Scopus). The findings indicate a significant increase in research since 2015, coinciding with the strengthening of the Sustainable Development Goals (SDGs) agenda, with dominant themes including green sukuk, Islamic social finance, ESG integration, and Maqasid al-Shari'ah. The findings also suggest that institutions in Malaysia, Indonesia, and the GCC countries have become the primary hubs for collaboration in the development of the discourse on sustainable Islamic finance. Nevertheless, empirical research on sustainability performance measurement based on Maqasid al-Shari'ah, as well as the concrete contribution of Islamic financial instruments to climate finance, remains limited. Conceptually, this study affirms that Sustainable Islamic Finance has the potential to become a global ethical financial paradigm capable of integrating Shari'ah values with economic, social, and environmental sustainability objectives.